Adherence to cardiac rehabilitation after acute coronary syndrome and its impact on patient outcome. (25th November 2020) - Sulzgruber, P; Sinkovec, H; Kazem, N; Hofer, F; Hammer, A; Koller, L; Todorovic, M; Katsch, F; Gall, W; Duftschmid, G; Heinze, G; Niessner, A
Abstract: Background: Secondary prevention after acute coronary syndrome (ACS) mirrors a key position in the reduction of morbidity and mortality in this highly vulnerable patient population. Especially cardiac rehabilitation proved to be one of the most beneficial therapeutic approaches for the reduction of re-events and overall modification of cardiovascular risk factors. However, profound epidemiological measures on adherence to a recommended cardiac rehabilitation after ACS remain scare, but seem of major importance in terms of preventing fatal cardiac adverse events. Therefore, we aimed to investigate adherence to cardiac rehabilitation after ACS and its impact on patient outcome from an Austrian nationwide perspective. Methods: Within this population-based national observation all patients presenting with ACS between 04/2011 and 8/2015 in Austria were enrolled. Patient characteristics and co-morbidities were assessed via the Austrian national health insurance system and elucidated according to ICD10 definitions. Adherence to recommended cardiac rehabilitation was investigated according to health insurance documentation. Patients were followed prospectively until the primary study endpoint (= mortality) was reached. Cox Regression hazard analysis was used to investigate the impact of non-adherence to cardiac rehabilitation on patient outcome and was adjusted for a comprehensive subset of confounders within the multivariate model. Results: During the observation period a total of 16.518 patients (median age: 64 years [54–74]; male: 68.4% [n=11.306]) met the inclusion criteria. Of alarming importance 86.6% (n=14.305) of all patients presenting with ACS did not perform any cardiac rehabilitation as recommended by current guidelines. During patient follow-up until 01/2018 a total of 1774 (10.7%) individuals died. Adherence to recommended cardiac rehabilitation had a strong an independent inverse association with mortality with an adjusted hazard ratio of 0.73 (95% CI: 0.54–0.98; p=0.036) (see Figure 1). Conclusion: The present nationwide investigation highlighted an overall low adherence to recommended cardiac rehabilitation after ACS. Since cardiac rehabilitation after ACS was associated with a 27% risk reduction for fatal cardiovascular events during the observation period, awareness in terms of cardiac rehabilitation and associated intensified risk factor modification should be promoted, in order to prevent fatal atherothrombotic events. Funding Acknowledgement: Type of funding source: None